2011
DOI: 10.3846/144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Price and Quality to Customer Satisfaction: Neuromarketing Approach

Abstract: The purpose of this article is to analyze literature and find out empirical evidence on product price and quality influence on customer satisfaction through neuromarketing approach. Customers’ satisfaction on their purchase is a significant factor that leads business to success. In recent times, customer satisfaction has gained new attention within the context of the paradigm shift from transactional marketing to relationship marketing. Even it is agreed in the literature that price and quality has high effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 5 publications
2
19
0
3
Order By: Relevance
“…According to Mowen and Minor (in Swastha, 2000: 21) [20] "consumer satisfaction is defined as the overall attitude shown by consumers for goods and services after they obtain and use". Related to this study, it has been proven that price and quality is an important factor for customer satisfaction which leads to marketing managers' decisions complexity nowadays as markets are becoming more and more complex and overloaded (Dapkevičius and Melnikas, 2009) [35]. For the location also proved that business location affects a business performance very significantly; it also has a significant effect on the repeat purchases of consumers (Eze et al, 2015) [32].…”
Section: Locationmentioning
confidence: 76%
“…According to Mowen and Minor (in Swastha, 2000: 21) [20] "consumer satisfaction is defined as the overall attitude shown by consumers for goods and services after they obtain and use". Related to this study, it has been proven that price and quality is an important factor for customer satisfaction which leads to marketing managers' decisions complexity nowadays as markets are becoming more and more complex and overloaded (Dapkevičius and Melnikas, 2009) [35]. For the location also proved that business location affects a business performance very significantly; it also has a significant effect on the repeat purchases of consumers (Eze et al, 2015) [32].…”
Section: Locationmentioning
confidence: 76%
“…Also, Dawes found that the price rise poses a potential threat to the establishment and maintenance of long-term customer relationships and loyalty (Dawes, 2009). Additionally, through a systematic review of the literature on the relationship between service price and customer satisfaction, we find conflicting research results: positive relationship (Clemes et al, 2008;Dapkevicius and Melnikas, 2009); negative relationship (Malik et al, 2012); inverted U-shaped relationship (Campo and Jesús Yagüe, 2009); no relationship (Mahmud and Jusoff, 2013;Pedraja Iglesias and Jesus Yagüe Guillén, 2004). Moreover, Liu found that price had a direct positive effect on online health consulting purchases (Liu and Ye, 2015).…”
Section: Development Of Paid Qanda Modelmentioning
confidence: 89%
“…In some circumstances, the customers are using the label or the price as an indicator of product quality [15]. Therefore, if the product has a leading label or the perceived price is raised, the perceived quality would also be increased [15,16]. These findings may have a significant impact for marketing and neuroeconomics.…”
Section: Consumer Neurosciencementioning
confidence: 99%